Multilateral benefit-sharing from digital sequence information will support both science and biodiversity conservation - Scholz, A.H.,; Freitag, J.; Lyal, C.H.C.; Sara, R.; Cepeda, M.L.; Cancio, I.; Sett, S.; Hufton, A.L.; Abebaw, Y.; Bansa, K.; Benbouza, H.; Boga, H.I.; et al. (Springer, 2022)
Open access to sequence data is a cornerstone of biology and biodiversity research, but has created tension under the United Nations Convention on Biological Diversity (CBD). Policy decisions could compromise research and development, unless a practical multilateral solution is implemented. Ensuring international benefit-sharing from sequence data without jeopardising open sharing is a major obstacle for the Convention on Biological Diversity and other UN negotiations. Here, the authors propose a solution to address the concerns of both developing countries and life scientists.